The Comparison of Vitamin C on Floral Herbal Kombucha During Shelf Life: Perbandingan Hasil Vitamin C Kombucha Bunga Herbal selama Masa Simpan - Lailatus Sa’diyah; Widya Dara Anindya; Fatma Ariska (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Kombucha is a probiotic herbal drink obtained from tea or herbal ingredients fermented by symbiotic bacteria and yeast for 7 days. The aim of this study was to obtain high vitamin C kombucha with various herbal ingredients such chamomile, lavender and chrysanthemum. This research was conducted by fermenting chamomile, lavender, and chrysanthemum flowers for 7 days, then stored for 7 days (after fermentation). Vitamin C levels were measured using UV-Vis Spectrophotometry at a maximum wavelength of 265nm. The results of vitamin C measurements in chamomile (Matricaria recutica), lavender (Lavandula angustifolia), and chrysanthemum (Chrysanthemum cinerariaefolium) kombucha after fermentation and 7 days of shelf life were decreased. The value of decreasing vitamin C were 22.59; 3.27; and 35.3, respectively. So, it can be concluded that chamomile, lavender, and chrysanthemum kombucha flower have different abilities to produce vitamin C. The highest vitamin C was produced by lavender herbal flower kombucha.